Adikmas Role Through Unit Dikyasa Figures In Pressing Traffic Violations By Senior High School Student In Jurisdiction Area Of Polres Rembang - Dadik Purnomo (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The title of this research is the Dikmas role through dikyasa units in suppressing the number of traffic violations by high school students in the Police Law Rembang. This study aims to the extent of the role played by Dikyasa Unit Police Traffic Unit in providing Dikmas Then Especially to students. This study uses the concept and theory as a knife analysis, which uses the concept of optimization, Dikmaslantas concept, the concept of prevention, the concept of traffic violations, the concept of students, operant conditioning theory, management theory, communication theory, and the theory of social control. With the conclusion of the implementation of Dikmas then still not optimal due to the persistence found the factors inhibiting the implementation of Dikmas So like; factors personnel, budgetary factors, factors of infrastructure, and the target location Dikmas factors that are difficult to reach. Therefore, all the inhibiting factors must be anticipated that the implementation of the activities can be carried out Dikmas necessarily optimal in reducing the number of traffic violations by high school students.Keywords: Dikmas; Traffic Violations; Dikyasa Unit; Senior High School Student.